2017
DOI: 10.1200/jco.2016.71.3289
|View full text |Cite
|
Sign up to set email alerts
|

Late Relapse of Classical Hodgkin Lymphoma: An Analysis of the German Hodgkin Study Group HD7 to HD12 Trials

Abstract: Purpose Clinical characteristics, therapeutic approaches, and prognosis of late relapse (LR) in patients with classic Hodgkin lymphoma (cHL) are poorly understood. We performed a comprehensive analysis of LR of Hodgkin lymphoma (LR-HL). Methods To estimate the incidence of LR-HL, we retrospectively analyzed 6,840 patients with cHL included in the German Hodgkin Study Group trials HD7 to HD12. Patients who experienced a relapse > 5 years into remission were compared with patients in continued remission for > 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 18 publications
2
42
2
Order By: Relevance
“…During the quest to omit RT, the relevant chemotherapy-associated morbidity 29,30 and late relapses of HL occurring especially in patients with earlystage disease should be acknowledged. 31 In the 50604 phase 2 trial, patients with nonbulky stage I/II disease with a negative interim PET/CT after 23ABVD (Deauville score, 1-3; 131 of 144 evaluable patients) were treated with an additional 23ABVD without consolidative RT, whereas patients with a positive interim PET/CT (12 of 144 patients) received 23BEACOPP escalated plus 30-Gy IFRT. Estimated 3-year PFS rates of 92% and 66%, respectively, for the PET 2 and PET 1 cohorts were reported in an interim analysis.…”
Section: Pet-adapted Strategiesmentioning
confidence: 99%
“…During the quest to omit RT, the relevant chemotherapy-associated morbidity 29,30 and late relapses of HL occurring especially in patients with earlystage disease should be acknowledged. 31 In the 50604 phase 2 trial, patients with nonbulky stage I/II disease with a negative interim PET/CT after 23ABVD (Deauville score, 1-3; 131 of 144 evaluable patients) were treated with an additional 23ABVD without consolidative RT, whereas patients with a positive interim PET/CT (12 of 144 patients) received 23BEACOPP escalated plus 30-Gy IFRT. Estimated 3-year PFS rates of 92% and 66%, respectively, for the PET 2 and PET 1 cohorts were reported in an interim analysis.…”
Section: Pet-adapted Strategiesmentioning
confidence: 99%
“…These results contradict the rationale of accepting a higher risk of relapse to achieve less toxicity, such as in the design of the H10 (Andre et al , ) and RAPID studies (Radford et al , ), and as in the report from the BC Cancer Lymphoid Cancer Database (Villa et al , ), where RT has been omitted for selected patients. There is an almost total absence of late relapses in contrast to other cohorts (Brockelmann et al , ). The lack of excess mortality needs to be confirmed in other cohorts.…”
Section: Discussionmentioning
confidence: 56%
“…The rate of relapses occurring later than 5 years after diagnosis was low, with only two late relapses, equal to a cumulative incidence of <1% at 10 years. This outcome seems to differ from the long‐term outcome in the GHSG studies (Brockelmann et al , ). In contrast to the Nordic registry, the GHSG clinical trials included patients with B‐symptoms and treatment with 20 Gy.…”
Section: Discussionmentioning
confidence: 72%
“…A late-relapse group had a better prognosis on survival than an early-relapse group within 5 years. 6 Early-relapse, defined as <1 year of a CR, is considered as a poor prognostic factor as well as refractory, B symptoms, extranodal involvement 8,9 and as a good indication for aPBSCT/HDT. Radman reported that in long-term results of conventional chemotherapy alone, a group showing a CR for more than 1 year showed better overall survival and relapse-free survival than a group showing a CR for <1 year (10-year overall survival of 37% vs 20% and relapse-free survival of 40% vs 18%, respectively; P < .01 and <.01, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A late-relapse group showing more than 5 years of a CR was also reported to have a better prognosis than an early-relapse group. 6 In the late-relapse group, a treatment option without aPBSCT/HDT would be reasonable, aiming for a sustained CR benefit and limiting toxicity and complications, including late nonrelapse mortality.…”
Section: Introductionmentioning
confidence: 99%